Framing Environmental Issues of Bangladesh in International Media: A Topic Modelling Analysis on the Guardian Newspaper - Mehedy Hassan Razib
Journalism has emerged as a crucial avenue for creating awareness of the increasing importance of addressing environmental risks that transcend national boundaries. This study examines the Guardian newspaper$1 (Bs coverage of environmental issues in Bangladesh, a country profoundly affected by climate change and natural disasters. Through analysing 345 news articles from 2011 to 2021, this research employs topic modelling to explore the international framing of climate concerns. The findings reveal thematic framing across various topics, including occupational environment, health and safety in the ready-made garment (RMG) industry, flooding along transboundary rivers, and Bangladesh$1 (Bs stance on the Paris Agreement and its approach to climate change. The Guardian emphasises ethical and sustainable practices in the fashion industry. It sheds light on the impact of flooding on vulnerable communities and discusses Bangladesh$1 (Bs energy policies in the context of global climate goals. Nevertheless, the study also highlights some limitations, such as the absence of comprehensive coverage of Bangladesh$1 (Bs diplomatic efforts at global climate forums and a lack of emphasis on developed nations$1 (Bresponsibility.s